The Link between Onset Age and Adult Offending: The Role of Developmental Profiles. Issue 9 (1st September 2016) - El Sayed, Sarah A.; Pacheco, Daniel F.; Morris, Robert G.
ABSTRACT: Studies of the development of anti-social behavior from adolescence through adulthood have suggested that early onset of offending tends to be associated with a lengthier criminal career. Recently, Bacon and colleagues uncovered a somewhat divergent finding in that late onset of delinquency was associated with subsequent offending among members of the 1958 Philadelphia Birth Cohort. This paper furthers this line of research by adopting a different methodological orientation, a finite mixture-modeling framework, to the 1958 Cohort data. Findings suggest that late adolescence onset of delinquency is associated with more offending in adulthood. Direction for future research is discussed.